Nocturnal dipping of heart rate and blood pressure in people with HIV in Tanzania - Nolan, C; Reis, K; Fadhil, S; Etyang, A; Ezeomah, C; Kingery, JR; Desderius, B; Lee, M-H; Kapiga, S; Peck, RN (Wiley, 2021)
People with HIV (PWH) have a >2-fold greater risk for development of cardiovascular disease (CVD), which may be associated with abnormalities in 24-h ambulatory blood pressure measurement (ABPM) profile. We conducted a nested case-control study of ABPM in 137 PWH and HIV-uninfected controls with normal and high clinic blood pressure (BP) in Tanzania. Nocturnal non-dipping of heart rate (HR) was significantly more common among PWH than HIV-uninfected controls (p = .01). Nocturnal non-dipping of BP was significantly more common in PWH with normal clinic BP (p = .048). Clinical correlates of nocturnal non-dipping were similar in PWH and HIV-uninfected adults and included higher BMI, higher CD4+ cell count, and high C-reactive protein for HR and markers of renal disease for BP. In conclusion, nocturnal non-dipping of both BP and HR was more common in PWH but further research is needed to determine causes and consequences of this difference.